Enterprise Architecture in E-Government: A Study of Integration Challenges and Strategic Opportunities - Hakimi, Musawer; Ghafory, Hamayoon; Fazil, Abdul Wajid (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Incorporating Enterprise Architecture (EA) into e-government frameworks shows potential for improving digital governance but poses notable difficulties. This study examines the intricacies and potential benefits associated with the incorporation of Enterprise Architecture (EA) into e-government projects. This study aims to investigate the level of enterprise architecture (EA) integration into e-government initiatives between 2016 and 2024 and provide insights into the obstacles and strategic opportunities associated with this integration. This research seeks to offer significant insights for policymakers, practitioners, and scholars on e-government by synthesizing existing material. We employed a methodical strategy, using the PRISMA selection process to collect and qualitatively combine 30 publications carefully. These publications were selected from a diverse pool of peer-reviewed articles, conference papers, and reports to conduct a thorough analysis of the integration of enterprise architecture in e-government. The literature research identified substantial barriers that impede the effective adoption of EA in e-government, including resistance within organizations, difficulties in leadership, limitations in resources, and complexities in technology. On the other hand, the analysis revealed strategic possibilities such as enhanced compatibility, scalability, and citizen-centric services, emphasizing Enterprise Architecture's revolutionary power in reforming governance procedures. To conclude, this study highlights the significance of tackling integration obstacles and using strategic possibilities to achieve the potential of EA in e-government fully. Policymakers and practitioners can utilize the knowledge acquired from this research to develop well-informed strategies for effectively managing the challenges of integrating enterprise architecture (EA) and attaining positive outcomes in digital governance. Future research should prioritize evaluating the applicability of integration solutions in different e-government settings and investigating the lasting effects of EA-driven digital governance on the quality of services and satisfaction of citizens